In situ coronary stent paving by Pluronic F127–alginate gel blends: Formulation and erosion tests. Issue 5 (21st May 2015) - Dalmoro, Annalisa; Barba, Anna Angela; Grassi, Mario; Grassi, Gabriele; Lamberti, Gaetano
Abstract: In this work the development of an experimental protocol to perform the in situ gel‐paving of coronary stent is presented. Biocompatible aqueous blends of Pluronic F127 and sodium alginates are used as potential drug dosage system for pharmacological in situ treatment of coronary in‐stent restenosis. Pluronic F127/alginate aqueous blend has the unique characteristic to be liquid at room condition and to form gel at physiological temperature. The proposed protocol is based on the blend injection on stent wall previously implanted in a flexible silicon pipe mimicking the coronary artery. Injected blend is warmed up until human body temperature achieving a soft gel, then it is reticulated by copper bivalent ions to obtain an hard gel. To test the gel paving resistance to erosion phenomena when it is exposed to fluid flux (i.e. blood flux) a dedicated device, (the Simulated Artery Device, SAD), was built to simulate the human circulatory apparatus. The SAD is an hydraulic circuit in which a buffer solution (at pH 7.4) was fluxed by a peristaltic pump through the pipe hosting the covered stent. Erosion tests were performed monitoring, by gravimetric and spectrophotometric methods, the residual mass anchored to stent mesh after given times. The obtained results showed that the in situ gel‐paving developed protocol was efficacious and reliable. The gel‐paving was completely eroded in a time of the same order of magnitude of the physiological period required to restore the coronary lesion (subsequent to the atheroma removal) and of a pharmacological therapy to inhibit the in‐stent‐restenosis pathology. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1013–1022, 2016.